Documentation of medicinal plant use in Karaj, Iran: An urban ethnobotanical study of herbal markets and shops - Jalali, Sahar; Ghahremaninejad, Farrokh; Nazari, Hamid; W. Bussmann, Rainer (Ethnobotany Research and Applications, 2026)
Background: Urban ethnobotany provides critical insights into how traditional plant knowledge adapts within modern societies. Despite Iran’s rich ethnomedicinal heritage, little attention has been paid to cities such as Karaj, where traditional and modern herbal markets coexist. Methods: Between 2018 and 2024, we surveyed 25 herbal outlets across 12 districts of Karaj. A total of 186 medicinal plant samples were collected, identified, and deposited as herbarium vouchers. Semi-structured interviews were conducted with herbalists and customers to document vernacular names, plant parts used, preparation forms, and therapeutic applications. Quantitative indices, including frequency and relative frequency of citation, were calculated to reveal use patterns. Results: The study recorded 186 species belonging to 144 genera and 68 families. The most represented families were Asteraceae (10%), Lamiaceae (9%), Apiaceae (8%), and Fabaceae (7%). Fruits (24.9%) and seeds (16.9%) were the most frequently traded parts. The dominant therapeutic categories included digestive (21.4%), immune/general tonic (17.7%), respiratory (10.1%), and nervous system (8.1%) uses. Native species constituted 57% of the recorded flora, while 33% were cultivated or imported. Conclusions: The herbal markets of Karaj demonstrate both continuity and transformation of traditional medicinal plant knowledge in an urban context. While long-established attari shops preserve vernacular expertise, modern outlets introduce packaged and imported products, reflecting shifts in consumer behavior and trade networks. These findings contribute to understanding urban ethnobotanical systems and emphasize the importance of documenting and safeguarding traditional medicinal knowledge within rapidly changing metropolitan environments. Keywords. Ethnobotany; medicinal plants; urban markets; Iran; Karaj; traditional knowledge